VD_FINDINFO Jug / 2012 / 170 vom 7. Februar 2012 - VD Tribunal cantonal (2012)
EXCÈS ET ABUS DU POUVOIR D'APPRÉCIATION, TORT MORAL, FAUTE PROPRE | 44 al. 1 CO, 47 CO, 398 al. 3 let. a CPP (CH), 398 al. 3 let. b CPP (CH)